Canada–US–Mexico Integration: Assessing (Im)Migrant Health Policy Convergence - Barnes, Nielan (International Journal of Canadian Studies / Revue internationale d’études canadiennes, 2011)
This paper uses a comparative case study approach to assess convergence between three areas of Canadian, US, and Mexican policy that shape (im)migrant access to health and social services. These three areas include key policies and programs in relation to Immigration and Citizenship rights; Temporary and Foreign Labour Visa Programs; and Health and Human Services programs and policies. The paper takes a meso-level approach and compares policy and programming trends among public and private organizational actors and fields in Canada, the US, and Mexico at societal, political and technical levels. Ultimately, the paper finds that despite local level innovation, there is a large degree of agreement in all three policy areas, as well as increasing convergence at social, political, and technical levels. Theoretically, the paper contributes to recent debates about how to assess policy convergence, as well as debates about the impact of globalization on policy convergence. Practically, understanding local dynamics of immigration and health policy convergence serves to develop realistic and informed policy and programs at the international, national, and local levels.